Analysis of Family Support and Patient Motivation in Diabetes Mellitus Diet Compliance - Nurwijayanti Nurwijayanti; Panca Radono (GLOBAL HEALTH SCIENCE GROUP, 2026)
Dietary adherence is a key pillar in the management of diabetes mellitus (DM) to prevent chronic complications. The phenomenon at RSU ‘Aisyiyah Ponorogo shows that even though patients have sufficient knowledge, many still have difficulty maintaining their diet. External factors, such as family support, and internal factors, such as patient motivation, are strongly suspected as determinants of the success of long-term dietary management. The purpose of this study is to examine how patient motivation and family support relate to dietary adherence in patients with diabetes mellitus at the Internal Polyclinic of RSU